Ancient Assyria a very short introduction - Radner, Karen 1972- (Very short introductions, 2015)
From city state to empire, in the early 2nd millennium BC to the end of the 7th century BC, Assyria was one of the most influential kingdoms of the Ancient Near East. Using archaeological discoveries from across the Middle East, Karen Radner demonstrates the vast, socially diverse, multicultural nature of Ancient Assyria and the Assyrian Empire